Effects of ingestion of bicarbonate, citrate, lactate, and chloride on sprint running - van Montfoort, M. C.; van Dieren, L.; Hopkins, W. G.; Shearman, J. P. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: Ingestion of sodium bicarbonate is known to enhance sprint performance, probably via increased buffering of intracellular acidity. The goal was to compare the effect of ingestion of sodium bicarbonate with that of other potential buffering agents (sodium citrate and sodium lactate) and of a placebo (sodium chloride) on sprinting. METHODS: In a double-blind randomized crossover trial, 15 competitive male endurance runners performed a run to exhaustion 90 min after ingestion of each of the agents in the same osmolar dose relative to body mass (3.6 mosmol x kg) on separate days. The agents were packed in gelatin capsules and ingested with 750 mL of water over 90 min. During each treatment we assayed serial finger-prick blood samples for lactate and bicarbonate. A familiarization trial was used to set a treadmill speed for each runner's set of runs. We converted changes in run time between treatments into changes in a time trial of similar duration using the critical-power model, and we estimated likelihood of practical benefit using 0.5% as the smallest worthwhile change in time-trial performance. RESULTS: The mean run times to exhaustion for each treatment were: bicarbonate 82.3 s, lactate 80.2 s, citrate 78.2 s, and chloride 77.4 s. Relative to bicarbonate, the effects on equivalent time-trial time were lactate 1.0%, citrate 2.2%, and chloride 2.7% (90% likely limits +/- 2.1%). Ingested lactate and citrate both appeared to be converted to bicarbonate before the run. There were no substantial differences in gut discomfort between the buffer treatments. CONCLUSION: Bicarbonate is possibly more beneficial to sprint performance than lactate and probably more beneficial than citrate or chloride. We recommend ingestion of sodium bicarbonate to enhance sprint performance.